2010
DOI: 10.1038/nrc2899
|View full text |Cite
|
Sign up to set email alerts
|

KRAS, Hedgehog, Wnt and the twisted developmental biology of pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by near-universal mutations in KRAS and frequent deregulation of crucial embryonic signalling pathways, including the Hedgehog (Hh) and Wnt–β-catenin cascades. The creation of mouse models that closely resemble the human disease has provided a platform to better understand when and in which cell types these pathways are misregulated during PDAC development. Here we examine the central part that KRAS plays in the biology of PDAC, and how the timing and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
435
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(452 citation statements)
references
References 122 publications
(113 reference statements)
13
435
1
3
Order By: Relevance
“…4A). Signaling pathways including PI3K/S6, ERK, STAT3, and β-catenin have been reported to be activated in PDAC (3,30,31). As expected, these pathways were prominently up-regulated in the PKC pancreata (Fig.…”
Section: Suppression Of Proliferation and Oncogenic Signaling In Pkc7supporting
confidence: 48%
“…4A). Signaling pathways including PI3K/S6, ERK, STAT3, and β-catenin have been reported to be activated in PDAC (3,30,31). As expected, these pathways were prominently up-regulated in the PKC pancreata (Fig.…”
Section: Suppression Of Proliferation and Oncogenic Signaling In Pkc7supporting
confidence: 48%
“…Wnt signaling regulates numerous aspects of pancreatic biology, and its activity is gradually increased during pancreatic carcinogenesis. The accumulation of b-catenin and activation of Wnt target genes have been observed in PanINs and PDAC (87,88). Inhibition of Wnt signaling has been shown to reduce proliferation and increase apoptosis of pancreatic cancer cells in vitro.…”
Section: Wnt/b-catenin Pathwaymentioning
confidence: 99%
“…Comprehensive genetic analysis [37][38][39] revealed that the Wnt is one of the six signaling pathways always altered in pancreatic cancers. [40] Its overexpression has recently been correlated to tumorigenesis, driving the self-renewal and differentiation of cancer stem cells and promoting the angiogenesis process [12,35,39,41,42]. On the basis of these observations, CKAAKN peptide, a specific Wnt-2 mimetic, may be considered as a novel promising homing device to tailor targeted nanoparticle towards pancreatic cancer cells.…”
Section: Ligand-receptor Interactionmentioning
confidence: 99%